Deflection of a γ-radiation beam produced by 900 MeV channeled electrons in a bent crystal - Adishchev Yu. N. Yuri Nikolaevich; Ananyin P. S.; Didenko A. N. Andrei Nikolaevich; Kalinin B. N.; Kaplin V. V. Valeriy Viktorovich; Rozum E. I.; Potylitsyn A. P. Alexander Petrovich; Vorobiev S. A. Sergey Aleksandrovich; Zabaev V. N. Viktor Nikolaevich (1980, 1980)
The angular distributions of photons produced by 900 MeV electrons channeled along the 〈111〉 axis of a silicon crystal were measured. A broadening of the angular distributions was observed in a bent crystal with radius R = 76 cm, which was caused most probably by the deflection of the channeled electron beam.